Pregnancy tumor: A rare case report in mandibular anteriors - Swati Phore; Rahul Singh Panchal (Wolters Kluwer Medknow Publications, 2017)
Pregnancy in a woman's life is associated with a variety of physiological, anatomical, and hormonal changes that can affect the cardiovascular, respiratory, and gastrointestinal systems. Such hormonal changes may lead to periodontal diseases and may be associated with generalized or localized gingival enlargements. Pregnancy does not cause the condition, but altered tissue metabolism in pregnancy accentuates the response to the local irritants, thereby causing gingival enlargements. In this report, a 25-year-old pregnant female had a localized gingival enlargement in the labial aspect of the mandibular anterior region.